2021
DOI: 10.3390/polym13060848
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of CeO2 Nanoparticles as Corrosion Inhibitor in Hybrid Biobased Waterborne Acrylic Direct to Metal Coating Binders

Abstract: CeO2 nanoparticles were incorporated in waterborne binders containing high biobased content (up to 70%) in order to analyze the anticorrosion performance for direct to metal coatings. Biobased binders were synthesized by batch miniemulsion polymerization of 2-octyl acrylate and isobornyl methacrylate monomers using a phosphate polymerizable surfactant (Sipomer PAM200) that lead to the formation of phosphate functionalized latexes. Upon the direct application of such binders on steel, the functionalized polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 53 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…52 Recently, Leiza and coworkers (Fig. 7c) 53 used batch miniemulsion copolymerization of 2-octyl acrylate and isobornyl methacrylate using a phosphate polymerizable surfactant (Sipomer PAM200) to form a novel hybrid CeO 2 bio-based (up to 70 wt%) acrylic binder for waterborne coatings. The phosphate groups were able to react with the metal surface, forming a layer at the substrate/coating interface achieving a better corrosion resistance.…”
Section: Vegetable-oil- and Lipid-based Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Recently, Leiza and coworkers (Fig. 7c) 53 used batch miniemulsion copolymerization of 2-octyl acrylate and isobornyl methacrylate using a phosphate polymerizable surfactant (Sipomer PAM200) to form a novel hybrid CeO 2 bio-based (up to 70 wt%) acrylic binder for waterborne coatings. The phosphate groups were able to react with the metal surface, forming a layer at the substrate/coating interface achieving a better corrosion resistance.…”
Section: Vegetable-oil- and Lipid-based Polymersmentioning
confidence: 99%
“…In the previous section, it was used as comonomer to prepare waterborne latex coating. 53,54 Luk and Maríc 86 synthesized poly(farnesene) homopolymer by nitroxide-mediated polymerization (NMP) in a miniemulsion using D7 (Dispolreg 007) or NHS-BB (succinimidyl-modified BlocBuilder) as alkoxyamine initiators. However, the final farnesene conversion was limited (30–40%), large particles were obtained (300–400 nm diameter size) in spite of the large amount of used Dowfax 8390 surfactant (15 wt% relative to monomer), the experimental M n for M n,target = 30 000 g mol −1 was significantly higher than the theoretical M n and the dispersity Đ was most often larger than 2.…”
Section: Terpene-based Polymersmentioning
confidence: 99%
“…Normally, anticorrosion properties of metallic structures are provided by developing metallic or non‐metallic coatings, which could act as a barrier with respect to metal surface and protect metallic structures from the environment. Therefore, a proper protective coating applied to mild steel is highly effective in corrosion inhibition 1–3 . In order to overcome the disadvantages of using hazardous materials as anticorrosion materials, inert organic coatings are preferred by numerous researchers 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] 2‐Octyl acrylate has successfully been used to develop waterborne adhesives [ 14–18 ] and coatings. [ 19–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[13] 2-Octyl acrylate has successfully been used to develop waterborne adhesives [14][15][16][17][18] and coatings. [19][20][21] However, the substitution of 2-EHA by 2-OA is not straightforward. Badía et al observed that for a pressure sensitive adhesive formulation, when comparing a formulation based on 2-OA with another one based on 2-EHA, a higher gel content was obtained for the 2-OA based formulation (75% gel content for 2-OA vs 52% gel for 2-EHA).…”
Section: Introductionmentioning
confidence: 99%